The Influence of Green Banking and ESG Practices on Financial Performance - Panjaitan, Raya; Siahaan, Jeremy; Julyanthry, Julyanthry (Institut Bisnis dan Informatika Kesatuan, 2025)
The purpose of this study is to examine how Indonesian state-owned banks' profitability was affected by green banking and Environmental, Social, and Governance (ESG) activities between 2021 and 2023. While ESG represents a dedication to environmental, social, and governance factors, green banking refers to ecologically friendly banking practices. This work employs panel data regression analysis on a sample using a quantitative methodology of five state-owned banks selected through purposive sampling, resulting in 30 observations from annual reports, sustainability reports, and Financial Services Authority data. The results show that green banking significantly increases bank profitability, while ESG practices separately do not have a significant impact. However, the integration of green banking and ESG simultaneously has a positive and significant effect on profitability. This finding implies that state-owned banks need to adopt a holistic sustainability strategy to optimize long-term financial performance. This integration not only supports financial stability but also strengthens the bank's contribution to sustainable development, in line with global goals for a better environment and responsible governance.